A Comparative Study of Mobile Internet Usage between the U.S. and Korea - Luke Yunkeun Shin (Journal of European Psychology Students, 2014)
The introduction of smartphones illuminated mobile internet prevalence, highlighting nomophobia. This study explored the mobile internet usage dependency of Korean and U.S. mobile users and investigated the severity of such usage dependency and the factors involved. In the combined data set, it was found that Korean users have higher usage dependency levels than US users and that students, unemployed users, and younger generations are more susceptible to mobile internet usage dependency. When comparing the two countries as separate data sets Korean females present as having higher usage dependency levels. In the U.S., it is students and younger generation groups who present with higher usage dependency levels. Regression analysis found that frequency of access has higher associations with mobile internet usage dependency than usage length. country of origin and age are significantly associated with mobile internet usage dependency.